2014
DOI: 10.1007/s00248-013-0354-5
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Thermoactinomyces Species in Selected Agricultural Substrates from Queensland

Abstract: Selected overheated substrates commercially available for public use in sub-tropical Queensland, Australia were screened for the presence of Thermoactinomyces species using an air sampler. All substrates with the exception of tea tree mulch were found to contain Thermoactinomyces species. Subsequent 16S rDNA oligonucleotide sequencing of the selected eight isolates indicated that some of these species were closely related to previously reported allergenic Thermoactinomyces vulgaris and Laceyella sacchari. In v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…The TAS amount in the unused bedding material from the store in winter 2017 was 1.96 log10 cfu/g, being lower than log10 cfu/g-values of the unused wood chips (<4.00-6.70 log10 cfu/g) identified by Driehuis et al [26]. Nevertheless, we also identified TAS spores in the stored bedding, as already shown [26,28]. Driehuis et al [26] postulated that TAS in stored products are due to the self-heating of the bedding material in the storage area.…”
Section: Bacterial Growth/identificationsupporting
confidence: 84%
See 3 more Smart Citations
“…The TAS amount in the unused bedding material from the store in winter 2017 was 1.96 log10 cfu/g, being lower than log10 cfu/g-values of the unused wood chips (<4.00-6.70 log10 cfu/g) identified by Driehuis et al [26]. Nevertheless, we also identified TAS spores in the stored bedding, as already shown [26,28]. Driehuis et al [26] postulated that TAS in stored products are due to the self-heating of the bedding material in the storage area.…”
Section: Bacterial Growth/identificationsupporting
confidence: 84%
“…The fact that the period between the complete renewal of the litter and the sampling day showed tendencies (p < 0.1; regression coefficient of −0.01 ± 0.00; Table S2) on the TAS concentration may be related to the fact that the fresh litter partly already contains TAS spores [26,28]. In the present study, we identified 1.96 log10 cfu TAS per g bedding material in one sample from the stock.…”
Section: Effects On the Amount Of Tas (Log10 Cfu/g Bedding Material)mentioning
confidence: 52%
See 2 more Smart Citations
“…However, a pilot study, carried out in September to October 1989 around Queensland sugar mills, concluded that workers in these environments presented with symptoms related to certain occupational lung disease29 . In a more recent study Brinkmann et al30 investigated selected overheated substrates commercially available for public use in sub-tropical Queensland in Australia and detected the presence of thermoactinomycetes (Figure 1). Subsequent molecular identification of the isolates confirmed their close relationship to previously reported allergenic Thermoactinomyces vulgaris and Laceyella sacchari.…”
mentioning
confidence: 99%